Patterns, socioeconomic inequalities and determinants of healthy eating in Kenya: results from a national cross-sectional survey - Elvis Omondi Achach Wambiya; Shukri F Mohamed; Lyagamula Kisia; Jane Osindo; Isaac Kisiangani; Patrick G Ilboudo; Hermann P P Donfouet; Samuel Kipruto; James Odhiambo Oguta (BMJ Open)
Objective The burden of non-communicable diseases is rising in low-and-middle-income countries, with diet being a key risk factor. This study aimed to assess the patterns, socioeconomic inequalities and determinants of eating healthy in Kenya. The study is the first in Kenya to use a healthy diet index to assess dietary patterns.Design and methods We analysed cross-sectional data from the 2015/16 Kenya Integrated Household Budget Survey. The study’s outcome variable was a continuous healthy diet index (HDI) constructed using principal component analysis from nine WHO/Food and Agriculture Organization (FAO) healthy diet recommendations. The HDI score and WHO/FAO healthy diet recommendations met were summarised for Kenyan households. Using the concentration index, we examined the socioeconomic disparities in healthy eating. In addition, multivariable linear regression was used to determine factors that influence healthy eating in Kenya.Results A total of 21 512 households in Kenya were included, of which 60% were rural and about two-thirds headed by males. The HDI score ranged between −1.13 and 1.70, with a higher value indicating healthier eating. Overall, the average HDI score was 0.24 (95% CI: 0.24 to 0.25), interpreted as moderate. We identified key determinants including socioeconomic status and urban–rural residency differences. Healthy eating was concentrated among higher socioeconomic households, regardless of gender or location. Higher socioeconomic status (β=0.28, 95% CI 0.26 to 0.30), rural residence (β=0.18, 95% CI 0.15 to 0.20), household head being in union (β=0.04, 95% CI 0.02 to 0.06) or employed (β=0.05, 95% CI 0.02 to 0.08) were significantly associated with increased HDI scores, whereas male-headed households and lack of education were associated with significant decreases in HDI scores on average.Conclusions Most Kenyan households do not meet all the healthy dietary recommendations, and socioeconomic inequalities exist in eating healthy. Targeted interventions that promote healthy eating based on key determinants in Kenya are required.